Comparison of in-line and off-line measurement systems using a calibrated industry representative artefact for automotive dimensional inspection. (15th October 2020) - Kiraci, Ercihan; Palit, Arnab; Donnelly, Michael; Attridge, Alex; Williams, Mark A.
Highlights: Measurement system capability study among CMM touch probe & laser scanner & in line laser radar. An industry representative artefact with actual Body-In-White features was used in the study. Developed an effective tolerance standard for auto-makers to assess measuring system capability. Abstract: Manufacturers should understand measurement system performance to identify and control measurement errors due to changes in the quality standard and actionable measurement data in the age of Industry 4.0. This study evaluates the capability of three measurement systems, determining their feature-specific suitability for automotive inspection. A touch-trigger probe CMM and a laser scanner CMM are compared as off-line measurement systems, against a laser radar as an in-line solution. Representative common automotive features were assessed using a calibrated industry artefact. The study shows the laser radar provides the comparable accuracy to off-line systems. If tolerances are smaller than ±1.5 mm, the capabilities of non-contact systems are considerably dependent on the measured feature type. This study provides improved understanding of the non-contact measurement system that would enable automotive manufacturers to implement fast measurement strategy based on feature definition and tolerance limit without reducing the quality of measurement.